Retrotranspositional landscape of Asian rice revealed by 3000 genomes - Carpentier, Marie-Christine (Nat Commun, 2019)
The recent release of genomic sequences for 3000 rice varieties provides access to the genetic diversity at species level for this crop. We take advantage of this resource to unravel some features of the retrotranspositional landscape of rice. We develop software TRACKPOSON specifically for the detection of transposable elements insertion polymorphisms (TIPs) from large datasets. We apply this tool to 32 families of retrotransposons and identify more than 50,000 TIPs in the 3000 rice genomes. Most polymorphisms are found at very low frequency, suggesting that they may have occurred recently in agro. A genome-wide association study shows that these activations in rice may be triggered by external stimuli, rather than by the alteration of genetic factors involved in transposable element silencing pathways. Finally, the TIPs dataset is used to trace the origin of rice domestication. Our results suggest that rice originated from three distinct domestication events.